"I HAVE NEVER TOUCHED IT": FLOUTING AND VIOLATION OF MAXIMS IN A COURT TESTIMONY - Dito Prasetyo, - (2018)
The present study examines the flouting and violation of maxims in a defendant's court testimony. It also investigates the possible reasons for flouting and violation of maxims committed by the defendant. The study employs a descriptive qualitative method in which the data of the study are in the form of transcripts of a defendant's full testimony in the session 26 regarding the court of Olivier café murder case. By employing Grice's (1975) theory of Cooperative Principle, the findings of the study show that the defendant flouted the maxims of quality, quantity, relation, and manner. It was also found that the defendant only violated the maxim of quality. This present study also found that the reason why the defendant flouted and violated the maxims was generally to prove and convince the audiences that she is innocent. The findings suggest that the defendant of the court tend to flout and violate the maxims in giving her testimony to yield hidden additional meanings and intentions in her utterances as well as to mislead her audiences.----Pembimbing Pendamping: Ernie D. A. Imperiani, M.Ed. Penelitian ini mengkaji pelanggaran maksim tipe flouting dan violation dalam sebuah kesaksian terdakwa. Penelitian ini juga mengkaji alasan dari pelanggaran maksim yang dilakukan oleh terdakwa. Penelitian ini menggunakan metode deskriptif kualitatif yang dimana data yang digunakan berupa transkrip dari kesaksian terdakwa di sesi 26 sidang kasus pembunuhan Olivier Café. Dengan menggunakan teori Prinsip Kooperatif dari Grice (1975), temuan dari studi ini menunjukan bahwa terdakwa melakukan pelanggaran maksim tipe flouting dengan maksim yang dilanggar adalah maksim kualitas, kuantitas, relasi, dan sikap. Penelitian ini juga menemukan bahwa terdakwa melakukan pelanggaran tipe violation pada maksim kualitas. Dari studi ini, ditemukan bahwa alasan terdakwa melakukan pelanggaran adalah untuk menunjukan dan meyakinkan peserta persidangan bahwa dia tidak bersalah. Implikasi yang ditemukan dari temuan ini adalah terdakwa persidangan cenderung melakukan pelanggaran maksim tipe flouting dan violation dalam memberikan kesaksian. Hal ini diperantarai untuk menghasilkan makna dan intensi tambahan.dan juga untuk menyesatkan peserta persidangan.